Activated PI3Kδ syndrome type 2: Two patients, a novel mutation, and review of the literature. Issue 6 (27th May 2016) - Olbrich, Peter; Lorenz, Myriam; Cura Daball, Paola; Lucena, José Manuel; Rensing‐Ehl, Anne; Sanchez, Berta; Führer, Marita; Camacho‐Lovillo, Marisol; Melon, Marta; Schwarz, Klaus; Neth, Olaf; Speckmann, Carsten
Abstract: Background: Autosomal dominant gain‐of‐function mutations in PIK3R1 encoding for the regulatory subunit (p85α, p55α, and p50α) of Class IA phosphoinositide 3‐kinase (PI3K) result in the activated PI3Kδ syndrome (APDS) type 2 characterized by childhood‐onset combined immunodeficiency, lymphoproliferation, and immune dysregulation. To improve clinical awareness and understanding of these rare diseases, we reviewed all hitherto published cases with APDS type 1 and type 2 for their clinical and immunologic symptoms and added novel clinical, immunologic, and genetic findings of two patients with APDS type 2. Methods: Clinical, immunologic, and genetic evaluation of two new patients with APDS2 was performed followed by the systematic collection of all available previously published data of patients with APDS1 and APDS2. Results: Patients with APDS type 1 (n = 49) and type 2 (n = 15) showed an indistinguishable immunologic phenotype. Overlapping clinical features shared by APDS type 1 and type 2 were observed, but our review also revealed previously unnoticed clinical differences such as remarkably high incidence of microcephaly, poor growth/short stature in patients with APDS2. Clinical management and outcome were variable and included prophylactic antibiotics, immunosuppression, immunoglobulin substitution, and hematopoietic stem cell transplantation. Conclusions: A disease‐specific registry collecting prospective and long‐term follow‐up data of patients with APDS, as currently set up by the European Society for Immunodeficiencies, are needed to better understand the natural history and to optimize treatment concepts and thereby improving the outcome of this heterogenous patient group.